2014
DOI: 10.1139/cjfr-2014-0168
|View full text |Cite
|
Sign up to set email alerts
|

Stumping trials in British Columbia — organic matter removal and compaction effects on tree growth from seedlings to midrotation stands

Abstract: There is considerable interest in understanding the repercussions of compaction and organic matter removal on soil quality and forest productivity. However, long-term field trials examining the effects of machinery and forest biomass removal on soil quality and stand regeneration are scarce. We present 20-31 years of tree growth results from four unique stump removal field trials. Each site had both treatments with varying amounts of organic matter removal (from tree stem harvesting to removal of tree stumps t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The compaction of the soil can generally influence the soil ecology negatively [17]. However, soil compaction causes physical changes that may not lead to significant changes in nutrient availability to plants [48]. This may be due to greater root-to-soil contact for nutrients; however, compaction usually reduces the lengthening of the primary root for nutrient absorption [49].…”
Section: Discussionmentioning
confidence: 99%
“…The compaction of the soil can generally influence the soil ecology negatively [17]. However, soil compaction causes physical changes that may not lead to significant changes in nutrient availability to plants [48]. This may be due to greater root-to-soil contact for nutrients; however, compaction usually reduces the lengthening of the primary root for nutrient absorption [49].…”
Section: Discussionmentioning
confidence: 99%
“…Third, stump removal may have negative ecological consequences (e.g. loss of organic compounds and nutrients in the soil) and increase the susceptibility of soil to erosion, both of which, in turn, affect the productivity of trees (Norris et al 2014;Achat et al 2015). Thus, this measure cannot always be considered as an efficient practical solution for Armillaria root disease management.…”
Section: Maximum Removal Of Roots By Machine Ripping and Removal Of Vmentioning
confidence: 99%
“…Soil has many physical and chemical properties, which can directly or indirectly affect vegetation, thereby leading to the establishment or enrichment of aboveground vegetation ( Russell and Beauchamp, 2017 ). Research has shown that the presence of soil organic matter confers high porosity, which can improve soil water retention and soil fertility and promote the growth of trees ( Norris et al., 2014 ). Soil temperature influences plant root biomass and drives how soil moisture content and pH value impact tree growth, which creates the conditions determining tree survival rates ( Greenwood et al., 2015 ; Nishar et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%